Thermal performance customization of polyimide films by nanocomposite engineering with Al2O3 and ZnO nanoparticles - Ashraf, Ahmad Raza; Akhter, Zareen; Farid, Muhammad Asim; Simon, Leonardo C.; Mahmood, Khalid; Nazar, Muhammad Faizan (Frontiers in Materials, 2025)
The fascinating properties of polyimide films, such as outstanding thermal stability, chemical/radiation resistance, excellent mechanical strength, and a low dielectric constant, can be further optimized by inorganic fillers, making them potential candidates for replacing metals/ceramics in modern technologies. In this study, the effect of Al2O3 and ZnO nanoparticles (NPs) on the thermal performance of polyimide was evaluated by varying nanoparticle loadings (3%, 5%, 7%, and 9%). The incorporation of nanoparticles within the polyimide matrix was confirmed by wide-angle X-ray diffraction (WAXRD) analysis. Their homogenous distribution throughout the matrix was verified by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Thermal decomposition of the polyimide matrix started at approximately 400°C, with relatively small weight loss up to 500°C, suggesting significantly high thermal stability. This stability was further improved by the addition of Al2O3 nanoparticles, while ZnO nanoparticles lowered the temperature resistance. The isothermal thermogravimetric analysis (TGA) further complemented the results of dynamic TGA as substantially high thermal endurance at 400°C was observed for polyimide nanocomposites, suggesting their capability to withstand elevated temperatures for extended periods. The glass transition temperature of the polyimide matrix was enhanced by both types of nanoparticles in a concentration-dependent manner. The thermal performance of polyimide was significantly affected by nanoparticle concentration.